Decline in values of degrees and recent evolution of wage inequality: Evidence from Chile - Murakami, Yoshimichi; Nomura, Tomokazu (Estudios de Economía, 2023)
Using data from nationally and regionally representative household surveys,we analyze the association between the changes in coefficients of dummy variables for higher education degrees in the wage equation and evolution of wage inequality in Chile from 2013-2017. Employing a decomposition method using unconditional quantile regressions, we find that a significant decline in the coefficients of professional degrees, especially from new private universities, with a larger magnitude at upper quantiles, is associated with a substantial reduction in wage inequality. The results are robust to the correction for sample selection bias and control for workers’ occupation and firm size categories.